2016
DOI: 10.1177/1539449216681277
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability and Internal Consistency of the Activity Card Sort–Australia (18-64)

Abstract: The Activity Card Sort (ACS) measures activity engagement levels. The Activity Card Sort-Australian version for adults aged 18 to 64 (ACS-Aus (18-64)) was recently developed, and psychometric properties have not yet been determined. This study was established to determine the test-retest reliability and internal consistency of the ACS-Aus (18-64) and describe activity engagement trends for healthy adults. Fifty-four adults aged 18 to 64 participated in this descriptive study. The ACS-Aus (18-64) demonstrated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…More participants identified as Australian/New Zealand ethnicity in this study (83.33% compared to 66.67%) and the distribution of participants across education levels was very similar. Due to a similar spread of demographics, this study appears to have the potential to demonstrate high levels of reliability as found for the card version of the ACS Aus (18-64) (Gustafsson et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…More participants identified as Australian/New Zealand ethnicity in this study (83.33% compared to 66.67%) and the distribution of participants across education levels was very similar. Due to a similar spread of demographics, this study appears to have the potential to demonstrate high levels of reliability as found for the card version of the ACS Aus (18-64) (Gustafsson et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
“…The next step was to examine participant experiences and the clinical utility of the app version. Before discussing the results, it is important to consider how the study demographics compare to those in the ACS Aus (18-64) study conducted by Gustafsson et al (2017). The distribution of participants across age groups in this study (18-44 years = 47.9%; 45-64 years = 52%) was more equitable than the age group distribution (18-44 years = 61%; 45-64 years = 38.9%) as reported by Gustafsson et al (2017).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations